Can Labor Emigration Affect the Education of Girls? Evidence from Tajikistan - Kseniia Gatskova; Artjoms Ivlevs; Barbara Dietz (Feminist Economics, 2019)
This study examines how large-scale, predominantly male emigration affects the education of girls staying in Tajikistan, the poorest post-Soviet state and one of the most remittance-dependent economies in the world. Using data from a three-wave household panel survey conducted in 2007, 2009, and 2011, this study finds that the net effect of migration on girls' schooling turns from positive to negative with girls' age. These results lend support to various conceptual channels through which the emigration of household members may affect girls' education, including the relaxation of budget constraints, a change of the household head, and an increase in household work. At the practical level, the results imply that migration can be detrimental to women's empowerment and cast doubt on whether emigration is an appropriate long-term development strategy for Tajikistan.
Keywords: F22; J16; J24; 330; girls' education; migration; remittances; female empowerment; Tajikistan